Proteomic Profiling of Mouse Helper T Cell Differentiation. Issue 7 (18th March 2019) - van den Ham, Henk‐Jan; Binai, Nadine A.; Zaaraoui‐Boutahar, Fatiha; Heck, Albert J. R.; Andeweg, Arno C.
Abstract: Helper T cell differentiation is a key process in the regulation of adaptive immune responses. Here, mouse Th1 and Th2 cells are profiled using high‐throughput proteomics to increase the understanding of the molecular biology of Th differentiation to support the design of prophylactic and therapeutic intervention strategies for (infectious) diseases. Protein profiling of Th1/Th2 differentiated cells results in the quantification of almost 6000 proteins of which 41 are differentially expressed at FDR < 0.1, and 19 at the FDR < 0.05 level, respectively. Differential protein expression analysis identifies a number of the expected canonical Th differentiation markers, and gene set analysis using the REACTOME database and a hypergeometric test (FDR < 0.05) confirms that helper T cell pathways are the top sets that are differentially expressed. Additionally, by network analysis, many differentially expressed proteins are associated with the Th1 and Th2 pathways. Data are available via PRIDE database with identifier PXD004532.